Influence of the stress-strain law modelling on the non-linear analysis of steel structures - Baptista, A. M. (2010)
This paper presents a study of the non-linear behaviour of a steel cross-section, using different stress-strain law representations and aimed at comparing their influence on the internal forces evolution. The study is carried out by means of an efficient non-linear model, based on the consideration of the cross-section global deformations. The results provide an evaluation of the benefits achieved by improving the constitutive law representation. Particular attention is paid to the situations in which the differences are more relevant.